HUBUNGAN LINGKUNGAN KELUARGA TERHADAP KARAKTER DISIPLIN DAN PRESTASI BELAJAR SISWA DI MI AL FIRDAUS LASEM SIDAYU GRESIK - Minahul Mubin (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This research is to find out 1. Relationship between Family Environment and Discipline Character and Student Learning Achievement at MI AL Firdaus Lasem Sidayu Gresik. 2. The relationship of learning discipline to the formation of character in students MI AL Firdaus Lasem Sidayu Gresik. This type of research is quantitative descriptive research. This study took the location at MI AL Firdaus Lasem Sidayu Gresik. Data collection techniques using a questionnaire technique. The data analysis technique used is multiple linear regression analysis, significance test of multiple linear regression (F test) and test the significance of the multiple linear regression coefficient (T test), In addition, the calculation of relative contributions and effective contributions is also carried out.The results of the regression analysis obtained the regression line equation: Y = 14,782 + 0,432X1 + 0,392X2. The equation shows that character building is influenced by the family environment and learning discipline. The conclusion of this research is 1. The family environment has a positive and significant effect on character building. Based on T test was obtained Tcount it > Ttabel, that is 6,342 > 1,980 and the value of the probability of significance < 0,05, that is 0,000. 2. Learning discipline has a positive and significant effect on character building. Based on F test noted that H0 rejected, becoause Fcount it > Ftabel, yaitu 49,342 > 3,072 and the value of the probability of significance < 0,05, that is 0,000. 3. Family environment variables make effective contributions 25,7%. Learning discipline variables make effective contributions 19,4%, so the total effective contribution is 45,1%, while 54,9% the rest is influenced by other variables not examined